Dietary polyphenols and sarcopenia: epigenetic mechanisms and geroscience perspectives for muscle health in aging - Da Silva Rodrigues, Guilherme; Lopes da Silva, Leonardo Santos; Crystine da Silva Sobrinho, Andressa; Benjamim, Jonas; Abud, Gabriela Ferreira; Ortiz, Gabriela Ueta; Cristini de Freitas, Ellen; Bueno Júnior, Carlos Roberto (Frontiers in Aging, 2026)
This review explores the effects of dietary polyphenols, such as resveratrol, quercetin, epigallocatechin gallate, and curcumin, on sarcopenia, with a particular focus on the underlying molecular and epigenetic mechanisms. These bioactive compounds may modulate key signaling pathways, including mTOR, NF-κB, and AMPK, while also influencing epigenetic processes such as DNA methylation, histone modifications, and microRNA regulation. Through these actions, polyphenols may reduce oxidative stress and chronic low-grade inflammation (inflammaging), enhance mitochondrial function, and contribute to the preservation of muscle mass and strength in older adults. Evidence from experimental and clinical studies investigating the impact of polyphenols on muscle health and their potential in the prevention or attenuation of sarcopenia will be discussed. In addition, current challenges and future perspectives will be addressed, emphasizing the role of epigenetic biomarkers and the potential synergy with physical exercise as part of integrated geroscience strategies to optimize muscle health during aging.